2021
DOI: 10.1093/annweh/wxab021
|View full text |Cite|
|
Sign up to set email alerts
|

Occupational Exposure to Diisocyanates in the European Union

Abstract: Objectives Diisocyanates are a chemical group that are widely used at workplaces in many sectors. They are also potent skin- and respiratory sensitizers. Exposure to diisocyanates is a main cause of occupational asthma in the European Union. To reduce occupational exposure to diisocyanates and consequently the cases of diisocyanate-induced asthma, a restriction on diisocyanates was recently adopted under the REACH Regulation in the European Union. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 53 publications
(51 reference statements)
0
23
0
Order By: Relevance
“…However, fewer data were available on the occupational exposure to diisocyanates in the manufacturing of other vehicles such as aerospace, shipping and large commercial vehicles, the construction sector, where there are potentially several sources of exposure (e.g., sprayed insulation, floor screeds), the use of MDI-based glues, and the manufacture of spray adhesives or coatings [ 11 ]. A recent review [ 6 ] also identified these sectors as potentially significant, based on airborne measurements of diisocyanate exposure (although several of these also have dermal contact potential). The current HBM4EU diisocyanates study, therefore, aimed to include these sectors, to harmonise the sampling strategy and ensure comparable analytical techniques.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, fewer data were available on the occupational exposure to diisocyanates in the manufacturing of other vehicles such as aerospace, shipping and large commercial vehicles, the construction sector, where there are potentially several sources of exposure (e.g., sprayed insulation, floor screeds), the use of MDI-based glues, and the manufacture of spray adhesives or coatings [ 11 ]. A recent review [ 6 ] also identified these sectors as potentially significant, based on airborne measurements of diisocyanate exposure (although several of these also have dermal contact potential). The current HBM4EU diisocyanates study, therefore, aimed to include these sectors, to harmonise the sampling strategy and ensure comparable analytical techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Diisocyanates have long been a leading cause of occupational asthma [5,6]. Exposure limits are generally very low (in the µg/m 3 range, https://limitvalue.ifa.dguv.de/, date accessed 13 July 2022), and the European Commission's Advisory Committee on Safety and Health at Work (ACSH) recently proposed a binding occupational exposure limit of 10 µg/m 3 (measured as -NCO, total reactive isocyanate groups), reducing it to 6 µg/m 3 from 1 January 2029 (https://circabc.europa.eu/ui/group/cb9293be-4563-4f19-89cf-4c458 8bd6541/library/0d11d394-b1e8-4e1a-a962-5ad60f4ab2ae/details, date accessed 13 July 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To reduce occupational exposure to diisocyanates and, consequently, the cases of diisocyanate-induced asthma, which is recognized as a particular problem in C.A.S.E. (Coatings, Adhesives, Sealants, Elastomers) applications, a restriction on the use of diisocyanates was recently adopted under the REACH Regulation in the European Union, allocating a three-year transition period [10,11]. Consequently, in recent years, considerable attention has been attributed to the development of modified or hybrid two-component adhesives, based on the use of two or more pre-polymers to meet high-performance criteria by combining best properties of individual polymeric counterparts within a joint composite system.…”
Section: Introductionmentioning
confidence: 99%
“…Isocyanate (N = C = O), a reactive chemical group that readily undergoes nucleophilic addition reactions, is essential to numerous industries [1,2]. Isocyanate groups attached to aromatic vs. aliphatic carbon backbones have distinct physical properties that influence their reaction products and industrial use [3][4][5][6]. Aromatic isocyanates primarily are used to produce solid and flexible polyurethane foam [7,8], however, its products are susceptible to damage by ultraviolet radiation and oxidation and are prone to discoloration over time [9].…”
Section: Introductionmentioning
confidence: 99%